(untitled) (Revista de Ciências Agroveterinárias, 2023)
The cultivation of offseason corn represents the largest planted area and production of the crop in Brazil since the 2011/2012 harvest, not being different in Tocantins. Corn is one of the main cereals produced in the world and one of the most demanding plant species in terms of N. The positive response to N is related to several biotic and abiotic factors and is the basis for constant studies, mainly in new agricultural frontiers. The objective of this work was to evaluate different doses of nitrogen fertilization in the cultivation of offseason corn in tow regions at Tocantins. For this purpose, two field experiments were installed (Palmas-TO; Lagoa da Confusão-TO), in the 2021/2022 off-season, in a randomized block design with four replications and six treatments (N topdressing doses: 0, 40, 80, 120, 160 and 200 kg ha-1). In Lagoa da Confusão-TO, grain yield showed a linear response with value of the 5.786 kg ha-1, with the use of the maximum dose (200 kg ha-1 of N in coverage), which were 104% higher when N was not used in coverage. In Palmas-TO, there was no significant effect of nitrogen on coverage and the average productivity was 6.632 kg ha-1. The characteristics related to seed quality showed no effect of nitrogen on coverage and correlation with agronomic characteristics. These, in turn, showed a strong association with grain yield.